Tratamento de efluentes de lavagem de ônibus e de lavanderia por flotação por ar dissolvido e filtração visando o reúso de água - Araujo, Ana Paula Cosso Silva (2017)
The intercity and interstate bus transportation chain requires services associated with car wash and laundry, for the washing of armchairs covers and blankets. Thus, this segment demands high consumption of water, combined to the use of chemicals that can compromise the quality of water resources. Water reuse is a technique that aims to reduce the consumption of drinking water for purposes that do not require such quality. Bus companies can deploy a reuse system in their bus wash units. However, adequate effluent treatment must be carried out so that the quality of the water produced does not negatively impact the activities of the unit where it is being reused, as well as the operators’ health. Therefore, this work aimed to promote the effluents treatment from a bus transportation company located in the city of Londrina, Paraná. The effluents used in this work are generated in the bus washing and laundry sectors, both activities carried out in the company. The treatability systems were evaluated on bench scale, being these: A) coagulation/flocculation/DAF system; B) coagulation/flocculation/DAF followed by post-treatment by granular filter media filtration under pressure; C) coagulation/flocculation/granular filter media filtration under pressure and D) granular filter media direct filtration under pressure, using the AQUAFLOC / LS and AQUA-PAC coagulants, aiming at the reuse of the treated effluent on the buses wash. The statistical design applied to the coagulation/flocculation/DAF assays was the Central Rotational Composite Design (CRCD). The independent variables applied were: AQUAFLOC/LS coagulant concentration, AQUA-PAC coagulant concentration, polymer concentration and pH coagulation. The coagulation/flocculation conditions applied for the DAF assays were: Gmr 800 s-1, G1ml 90 s-1, G2ml 50 s-1 and G3ml 30 s-1, corresponding to the rotation times of 1; 10; 5 and 5 minutes, respectively. The pressure in the saturation chamber was 6 bar, the recirculation rate used was 20% and the rates of surface application were 35, 70, 120 and 150 m3 m-2 day-1. For the coagulation/flocculation/filtration tests, the coagulation/flocculation conditions were: Gmr 800 s-1 and G1ml 50 s-1. For the filtration tests, a bench scale granular filter under pressure was prepared containing sand and gravel filter material. The treatability systems were evaluated in relation to the organic matter removal, solids, nitrogen, phosphorus and surfactants. Through the application of the CCDR method, an optimum range of coagulant action in the effluent treatment was determined. By promoting the mixing of the effluents from both sectors for subsequent treatment, the optimum concentration range of the AQUAFLOC/LS coagulant varied from 220 to 260 mg L-1 with a natural coagulation pH, while the optimum concentration range of AQUA- PAC are between 50 and 200 mg Al2O3 L-1 with coagulation pH from 6.00 to 7.50 and between 200 and 320 mg Al2O L-1 with coagulation pH from 8.30 to 9.00. For the treatment of bus washing effluent, the optimum AQUAFLOC/LS concentration varied between 55 and 110 mg L-1 with coagulation pH from 6.00 to 7.20, the AQUA-PAC concentration ranged from 65 to 85 mg Al2O3 L-1 with natural coagulation pH. Finally, for the laundry effluent treatment, the optimum AQUAFLOC/LS concentration range varied from 200 to 400 mg L-1 with a coagulation pH from 8.90 to 9.00, and for AQUA-PAC, the optimum range concentration varied from 600 to 700 mg Al2O3 L-1 with 11 coagulation pH from 7.2 to 7.6.When evaluating the different treatability systems, it was verified that the coagulation/flocculation/DAF systems followed by filtration and coagulation/flocculation/filtration using the AQUAFLOC/LS coagulant presented the highest reduction indices of the analyzed parameters with reduction efficiencies of COD ranging from 73% to 81%, turbidity between 93% and 94%, suspended solids from 16% to 100% and surfactant from 90% to 98%.The granular filter media filtration system under pressure made it possible to obtain treated effluents that could be reused in bus washing services.